A study of maternal outcome in first trimester bleeding - Bala, Neerupham; Kaur, Navneet; Shifali, Anand; Wakhloo, Ajay; Tabassum, Nazia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The outcome of first trimester vaginal bleeding is a matter of debate. Vaginal bleeding is common and potentially alarming symptom in early pregnancy. First trimester bleeding is a common occurrence. It has been estimated to occur in 15-25% of all pregnant women. Objective of this study was to evaluate the various maternal outcomes in women with first trimester bleeding. Methods: This prospective observational study was conducted in the postgraduate department of obstetrics and gynecology, SMGS Hospital, Government Medical College, Jammu, Jammu and Kashmir, India. The study included 200 pregnant women presented with first trimester bleeding. All the women were followed prospectively till delivery and early postpartum period for various outcomes such as preterm delivery, PROM, PPROM, anemia, oligohydramnios, placental abruption, placenta previa and postpartum hemorrhage. Results: Out of 200 patients studied, 19% patients aborted. Ectopic and molar pregnancy was seen in 5% and 1.5% patients respectively. Out of 74.5% patients who continued pregnancy, maternal complications included anemia (52%), PROM (14.09%), oligohydramnios (6.71%), placenta previa (5.37%), PPH (4.03%), PPROM (2.68%), preeclampsia (2.01%), gestational hypertension (1.34%), abruption and post-datism (0.67% each). Conclusions: From the results of this study, it can be concluded that first trimester bleeding can be a predicting factor in terms of mother and infant consequences of pregnancy and it is necessary to increase the knowledge of pregnant women in this regard for closer care.